T cell memory. Skin-resident memory CD8⁺ T cells trigger a state of tissue-wide pathogen alert - Ariotti, Silvia; Hogenbirk, Marc A; Dijkgraaf, Feline E; Visser, Lindy L; Hoekstra, Mirjam E; Song, Ji-Ying; Jacobs, Heinz; Haanen, John B; Schumacher, Ton N (Science (American Association for the Advancement of Science), 2014)
After an infection, pathogen-specific tissue-resident memory T cells (T(RM) cells) persist in nonlymphoid tissues to provide rapid control upon reinfection, and vaccination strategies that create T(RM) cell pools at sites of pathogen entry are therefore attractive. However, it is not well understood how T(RM) cells provide such pathogen protection. Here, we demonstrate that activated T(RM) cells in mouse skin profoundly alter the local tissue environment by inducing a number of broadly active antiviral and antibacterial genes. This "pathogen alert" allows skin T(RM) cells to protect against an antigenically unrelated virus. These data describe a mechanism by which tissue-resident memory CD8(+) T cells protect previously infected sites that is rapid, amplifies the activation of a small number of cells into an organ-wide response, and has the capacity to control escape variants.